The Role of Sleep in Fear Learning and Memory - Davidson, Per (Curr Opin Psychol, 2019)
During the last 10 years, a large body of studies have used fear conditioning paradigms to study the role of sleep in the consolidation of fear and safety learning. This line of research could allow us to answer if it is adaptive or not to sleep in the aftermath of a negative experience, and if sleep has a role in consolidating extinction learning. This field has so far produced several contrasting findings. Thus, this review will not deliver many clear conclusions, but will instead be an attempt to summarize what we know at the moment, to describe the potential clinical applications of this research, and to discuss where to go from here.